2019
DOI: 10.1080/10538712.2019.1678542
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Dysregulation in Sexually Abused Preschoolers: Insights from a Story Completion Task

Abstract: Child sexual abuse (CSA) during the preschool period can seriously undermine children's ability to develop emotional competency (Cicchetti & Toth, 1995). Narrative tasks, such as the MacArthur Story Stem Battery (MSSB), are particularly adapted to gain a better understanding of young children's self-regulation processes (Holmberg et al., 2007). To explore the emotion regulation competencies of sexually abused preschoolers, we developed a coding grid and undertook a detailed analysis of abused and non-abused ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Dissociation was defined by Spiegel and Cardena (1991) as "a structured compartmentalization of mental processes (e.g., thoughts, emotions, conation, memory, and identity) that are typically integrated" and is known to have long lasting deleterious consequences on multiple domains of children 's functioning (e.g., school, interpersonal;Silberg, 2014). Consistent with the CPTSD model, other consequences have been documented in sexually abused children (e.g., emotional dysregulation, sleep problems, insecure attachment patterns, somatic complaints; e.g., Charest et al, 2019;Langevin et al, 2019) but given the centrality of behavior problems and dissociation and their deleterious impacts on developmental trajectories (e.g., Colman et al, 2007;Reef et al, 2010), these will be the focus of the current investigation. Notably, a literature review concluded that 10%-53% of sexually abused children do not present difficulties following the abuse (Domhardt et al, 2015).…”
Section: Consequences Of Csamentioning
confidence: 97%
See 1 more Smart Citation
“…Dissociation was defined by Spiegel and Cardena (1991) as "a structured compartmentalization of mental processes (e.g., thoughts, emotions, conation, memory, and identity) that are typically integrated" and is known to have long lasting deleterious consequences on multiple domains of children 's functioning (e.g., school, interpersonal;Silberg, 2014). Consistent with the CPTSD model, other consequences have been documented in sexually abused children (e.g., emotional dysregulation, sleep problems, insecure attachment patterns, somatic complaints; e.g., Charest et al, 2019;Langevin et al, 2019) but given the centrality of behavior problems and dissociation and their deleterious impacts on developmental trajectories (e.g., Colman et al, 2007;Reef et al, 2010), these will be the focus of the current investigation. Notably, a literature review concluded that 10%-53% of sexually abused children do not present difficulties following the abuse (Domhardt et al, 2015).…”
Section: Consequences Of Csamentioning
confidence: 97%
“…Intergenerational cycles of CSA warrant independent examinations given the unique nature of this form of maltreatment, including the fact that perpetrator is not necessarily a caregiver and the unique traumagenic dynamics of sexualization, betrayal, stigmatization, and powerlessness involved ( Finkelhor & Browne, 1985 ). Cycles of CSA, as compared to other forms of maltreatment, are understudied ( Langevin et al, 2019 ). While our study does not allow to identify mechanisms of intergenerational continuity of CSA, it will fill some important gaps in the literature and further our understanding of the mechanisms involved in the associations between maternal history of CSA and sexually abused children’s outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Childhood trauma is an experience that has lasting and substantial psychosocial and somatic impacts on a child including on school functioning (e.g., lower grades, educational attainment) (Mitchell et al, 2021), attachment styles (Cyr et al, 2010), and emotion regulation (Langevin et al, 2020). Mental health problems, such as symptoms of anxiety, depression, sleep problems, and post-traumatic stress are common following CSA (Gardner et al, 2019;Langevin et al, 2022).…”
Section: Adult Dyadsmentioning
confidence: 99%
“…Örselenme yaşantıları üzerine yapılan çalışmalar, bu olumsuz deneyimlerin bireylerin yaşantılarında olumlu benlik algısının zedelenmesi, kaygı bozuklukları, madde kullanımı, disosiasyon, öfke problemleri, kişilik bozuklukları, yeme bozuklukları, obsesif kompulsif bozukluk, travma sonrası stres bozukluğu, somatizasyon, kişiler arası ilişkilerde problemler, psikolojik iyilik halinin bozulması ve depresif belirtileri artması gibi etkilerinin olduğunu göstermektedir [15][16][17] . KZVD de bu etkiler arasında yer almaktadır 17 .…”
Section: Introductionunclassified